(untitled) (Eurasian Scientific Herald, 2023)
This article explores the development of teaching skills in English, specifically focusing on terms related to tourism. The study employs an integrated approach that combines various pedagogical methods to enhance language acquisition and communicative competence among learners. The article discusses the literature related to English language teaching in the context of tourism, presents the methods used in the study, analyzes the results, and concludes with suggestions for further improvement.